A new poly(I:C)-decorated PLGA-PEG nanoparticle promotes Mycobacterium tuberculosis fusion protein to induce comprehensive immune responses in mice intranasally. (January 2022) - Du, Xiufen; Tan, Daquan; Gong, Yang; Zhang, Yifan; Han, Jiangyuan; Lv, Wei; Xie, Tao; He, Pu; Hou, Zongjie; Xu, Kun; Tan, Jiying; Zhu, Bingdong
Abstract: Protein-based subunit vaccine against tuberculosis (TB) is regarded as safer but with lower immunogenicity. To investigate effective adjuvant to improve the immunogenicity of TB subunit vaccine, we modified ploy(I:C) onto PLGA-PEG copolymer nanoparticle with polydopamine to produce a new nanoparticle adjuvant named "PLGA-PEG-poly(I:C)" (NP). M. tuberculosis fusion proteins Mtb10.4-HspX and ESAT-6-Rv2626c (M4) were encapsulated in the nanoparticles to produce the NP/M4 subunit vaccine. The PLGA-PEG/M4 nanoparticle was 200.21 ± 1.07 nm in diameter, and the polydispersity index (PDI) was 0.127 ± 0.02. Following modification with poly(I:C) by polydopamine, the NP/M4 was administered to C57BL/6 female mice intranasally and the immune responses were evaluated. The NP/M4 significantly induced antigen-specific CD4 + T cells proliferation, IL-2 and IFN-γ production. In addition, the NP/M4 could promote the production of antigen-specific IgG, IgG1, IgG2c in serum, and sIgA in lung washings. Overall, our results indicated that the NP would be a potential TB subunit vaccine adjuvant with the ability to induce strong Th1-type cell-mediated immunity and humoral immune responses. Graphical abstract: Image 1 Highlights: Formulation contained PLGA-PEG-poly(I:C) nanoparticles can induce the mucosal immunity. PLGA-PEG-poly(I:C) nanoparticles can improve the production of IL-2 and IFN-γ. PLGA-PEG-poly(I:C) nanoparticles have potential adjuvant effects and promote the cellular and humoral immune responses.